MAQASID SYARIAH ANALYSIS OF INDONESIA’S 2025 HAJJ COST POLICY - Nur Azizah; Adamu Abubakar Muhammad (Institut Agama Islam Negeri Metro, 2026)
This study analyzes Presidential Decree Number 6 of 2025 concerning the Cost of Organizing the Hajj (BPIH) for 1446 H/2025 AD, which establishes a new Hajj cost structure based on Hajj Travel Costs and Benefit Value. The study employs a normative legal approach using three methods: a statute approach to examine Presidential Decree No. 6/2025 and related regulations, a comparative approach to compare Indonesia’s Hajj cost policy with those of other countries, and a fiqh approach to evaluate its conformity with the principles of maslahah (public benefit) and the prevention of mafsadat (harm). Data were collected through a literature review of relevant books, journals, fatwas, and legal documents. The findings indicate that although the 2025 Hajj cost policy aims to promote public benefit, its implementation has not fully reflected the fiqh principle of Tasharruf al-Imam 'ala al-Ra'iyyah Manuthun bi al-Maslahah. The imbalance between achieving benefits and preventing adverse impacts, particularly the financial burden on lower-income prospective pilgrims, limits the realization of maqasid al-shariah. Consequently, the policy has not optimally fulfilled the principles of justice (al-'adl) and protection of wealth (hifzh al-mal). The study recommends improving future Hajj cost policies through a better balance between maslahah and mafsadat, with public participation.